Significance of detecting cardiac troponin I and creatine kinase MB in critically Ill children without primary cardiac illness - Zhang, Yangyang; Cao, Yinyin; Xin, Yi; Liu, Yongming (Frontiers in Pediatrics, 2024)
Objective: To investigate the incidence of myocardial injury in children with non-cardiac-origin critical illness and the association between elevated cardiac troponin I (cTnl) and creatine kinase MB (CK-MB) concentrations on disease progression and prognosis to guide early treatment. Methods:The serum cTnI and CK-MB concentrations of 292 children with non-cardiac-origin critical illness in Yantai Yuhuangding Hospital between January 2021 and January 2024 were retrospectively analyzed within 24 hours after entering the Pediatric Intensive Care Unit (PICU). The children were divided into the normal and abnormal myocardial marker groups according to the results. The abnormal myocardial marker group was further divided into the cTnI-elevated, CK-MB-elevated, singleelevated (cTnI-or CK-MB-elevated) and double-elevated (cTnI-and CK-MB-elevated) groups. The differences in the clinical indicators and their relationships with prognosis for the groups were compared. Results: The incidence of myocardial injury among the children with non-cardiac-origin critical illness was 55.1% The incidence of myocardial injury in children with infectious diarrhea combined with moderate and severe dehydration reached 85.19%. The pediatric critical illness score; frequency of use of vasoactive drugs; low heart sound, hypotension, shock, heart failure, respiratory failure, and multiple organ dysfunction syndrome; and mortality indexes differed significantly for the normal and abnormal myocardial marker groups (P < 0.05). The single-elevated and normal groups only showed a difference in the mortality rate (P < 0.017). The cTnI and CK-MB concentrations were negatively correlated with prognosis (P < 0.01). Conclusion: Myocardial injury is common in children with non-cardiac-origin critical illness. Children with infective diarrhea concurrent with moderate and severe dehydration in the PICU are more likely to suffer myocardial injury. Both CK-MB and cTnI are useful for early diagnosis and monitoring of myocardial injury, and their combined detection is more meaningful. Elevated serum cTnl and CK-MB concentrations often indicate that children have more severe disease; and have higher risks of poor prognoses and mortality. The insights will guide the treatment and improve the prognosis. This investigation is a retrospective case-control study, which covers certain limitations. A further validation through multi-center, clinical, prospective, observational research is required to corroborate the findings.